ANTIBACTERIAL POLY-HERBAL SEMISOLID FORMULATIONS CONTAINING LEAVES EXTRACTS OF TECTONA GRANDIS, MANGIFERA INDICA AND ANACARDIUM OCCIDENTALE (International Journal of Pharmaceutical Sciences and Drug Research, 2016)
Herbal medicine have become an item of global importance both has medicinal and economical value. Plants used for medicinal purposes long before recorded history. Many plant species have been proved to have antibacterial activity. Thus, the main objective of the study was to formulate and evaluate a poly-herbal semisolid dosage forms using ethanolic extracts of frontal leaves of T. grandis, M. indica and A. occidentale. Formulations were evaluated for its physicochemical properties like color, consistency, pH, spreadability, extrudability and the results were found satisfactory. Antibacterial activity of formulations was studied against S. aureus, E. coli and P. aeruginosa by agar well diffusion method. (E. coli, P. aeruginosa) bacteria. The order of activity was as follows: Water Soluble bases > Gel Bases > Hydrocarbon Bases. The zones of inhibition of poly herbal formulations were in between 23-28 mm which can be comparable with standard formulation 24-29 mm. Activity of the formulations may be due to the presence of alkaloids, flavanoids, phenols and tannins in the extracts. The formulations were found to be very efficacious in all the parameters.